PROGRAM APLIKASI KLASIFIKASI PENGGUNAAN LAHAN PERTANIAN DAN PENUTUP LAHAN DENGAN MODIS SINTETIK - Ricky Alberta (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Land is a natural resource that acts as a container and production factor for humans; it also acts as a place for activities, survival and a place to earn a living. With the development of infrastructure and increase in population results in an increase space of land needed. The help of remote sensing science results in all sorts of information regarding the land, and gives an idea of the classification of land usage and cover. This research covers the classification of usage of paddy fields and those outside of paddy fields. Land cover will be divided into 3 classes; empty fields, foliage, and buildings in the Karawang area North Java. The classification process is divided into 2 phases, which is training and testing phases. During the training classification, the data used will be ground based which will be used as training data and will be using Kurtosis Projection Method. The training cover classification of land will use Google Earth data that displays high resolution pictures that will show the closure of these lands as a training data. The testing phase will be using MODIS image data with the parallelepiped classification method and the minimum distance for the classification process of the land cover. The results of the test classification of usage of land will result a true average of 83.14% and the classification land cover will result a true average of 88.27%. Key words Ground Based, Google Earth,Kurtosis projection, Land, Land Cover, Land Usage,Minimum Distance, MODIS Image, Parallelepiped Classification, Remote Sensing